2012
DOI: 10.1007/s00604-012-0878-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of aminoglycoside antibiotics using an on-chip microfluidic device with chemiluminescence detection

Abstract: We describe an on-chip microflow injection (μFI) approach for the determination of aminoglycoside antibiotics using chemiluminescence (CL) detection. The method is based on the inhibition of the Cu(II)-catalyzed CL reaction of luminol and hydrogen peroxide by the aminoglycosides due to the formation of a complex between the antibiotic and Cu(II). The main features of the method include small sample volumes and a fast response. Syringe pumps were used to insert the sample and the reagents into the microfluidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…A comparison of the proposed method features with those of other previously reported methods for AAG determination is shown in Table . As can be seen, few methods used microfluidic systems , or liposomes, , and no methods used the combination of both methods for the AAGs determination. The LOD reached using a microfluidic system with liposomes magnetically retained is lower than those obtained using these methodologies separately.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of the proposed method features with those of other previously reported methods for AAG determination is shown in Table . As can be seen, few methods used microfluidic systems , or liposomes, , and no methods used the combination of both methods for the AAGs determination. The LOD reached using a microfluidic system with liposomes magnetically retained is lower than those obtained using these methodologies separately.…”
Section: Resultsmentioning
confidence: 99%
“…For the off-chip coupling, several approaches have been described. The use of bifurcated optical fiber guides or x – y – z alignment devices involved studying a high number of variables, apart from the requirement of voluminous and costly equipment for the coupling. , An alternative is an off-chip option involving integrating the microfluidic chip focused on the optical pathway of a conventional detector using 3D-printed alignment devices …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For field applications, microfluidics or paper-based chemical assays can also be used. For example, Sierra et al [ 37 ] reported a microfluidic system that measures chemiluminescent output related to the interaction between aminoglycoside antibiotics and copper ions on a chip. The limit of detection for this method was below 1 ng/mL.…”
Section: Conventional Methods Of Antibiotic Detection and Food Contam...mentioning
confidence: 99%
“…Luminol-H 2 O 2 -Cu(II) is a well-known CL reaction (28). This reaction has been exploited for the determination of several aminoglycoside antibiotics including amikacin, streptomycin, kanamycin B, paromomycin and neomycin B (29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%